Lack of law that accommodates project bundling as an effort to increase the feasibility of road procurement through a cooperation scheme between the government and small-scale business entities (KPBU) - Andi Fachriyanto; Sadino Sadino; Anis Rifai (Universitas Wiralodra, 2023)
Provision of road infrastructure at local and regional level is still having a problem in financing and public private partnership (PPP) still cannot solve the problem. Project bundling for PPP is a great option to improve the financial feasibility of smaller value projects. It may be appropriate for the PPP legal framework to provide and support bundling, to make project bundling run smoothly, in order, and achieve its original purpose. This paper is trying to see if the laws and regulations for PPP can provide and support project bundling. The methods used are normative juridical by legislation approach and conceptual approach. This paper concludes that the law providing PPP cannot yet support project bundling properly, caused by the lack of law and inconsistencies in Indonesian Ministerial Regulations that regulates PPP. This calls for a law revision or at least an intervention by policies to support bundling for smaller projects.